Previous infestation with Psammotettix alienus on spring wheat seedlings decreased the fitness of Sitobion avenae in a subsequent infestation. (8th October 2015) - Luo, Kun; Thieme, Thomas; Hu, Zuqing; Hu, Xiangshun; Zhang, Gaisheng; Zhao, Huiyan
Abstract: Previous feeding by herbivores may influence the performance of other herbivores by altering the morphological and physiological properties of the shared host. The present study aimed to examine the fitness of the apterous aphid Sitobion avenae (Fabricius) (Hemiptera: Aphididae) when fed spring wheat that was previously attacked by the leafhopper Psammotettix alienus Dahlbom (Hemiptera: Cicadellidae), with an evaluation of the differences in aphid weight ( WD ), development time ( D ), mean relative growth rate ( MRGR ), daily production of nymphs ( MDNP ) and intrinsic rate of population increase ( r m ) under controlled greenhouse conditions. For the S. avenae reared on the two spring wheat cultivars that were previously infested with P. alienus, the WD and the MRGR decreased significantly. The S. avenae reared on the previously infested cv. Leguan had significantly prolonged D values and a lowered r m, whereas these parameters did not differ significantly when S. avenae was reared on the cv. Bobwhite . Overall, the fitness of the aphid S. avenae was adversely affected when reared on the two spring wheat cultivars that were previously infested with P. alienus .